Exposing human primary dermal fibroblasts to particulate matter induces changes associated with skin aging. Issue 11 (11th September 2020) - Reynolds, Wil J.; Hanson, Peter S.; Critchley, Adam; Griffiths, Ben; Chavan, Bhaven; Birch‐Machin, Mark A.
Abstract: With a large proportion of the world's population living in areas where air quality does not meet current WHO guidelines, combined with the knowledge that pollutants can interact with human skin, it is now of even greater importance that the effects of air pollutant exposure on human skin be investigated. To evaluate the damaging effects of a known component of air pollution (particulate matter) on human primary dermal fibroblasts. These studies were undertaken by exposing primary human dermal fibroblasts to different concentrations of particulate matter and analyzing the effects over time using resazurin reduction assays. Immunofluorescence microscopy was used to determine if particulate matter caused activation of the aryl hydrocarbon receptor, and phosphorylation of histone H2AX, a known marker of double‐strand DNA breaks. Dot blotting was also used to analyze expression changes in secreted MMP‐1, MMP‐3, and TGFβ. Particulate matter was found to dose‐dependently increase cellular viability, activate the aryl hydrocarbon receptor, increase double‐strand DNA breaks, and increase the expression of MMP‐1, MMP‐3, and TGFβ. With the potential of air pollutants such as particulate matter to not only modulate the expression of proteins implicated in skin aging, but also affect cells at a genetic level, brings a pressing need for further investigation so protective strategies can be implemented.